2008
DOI: 10.1109/tac.2008.2007862
|View full text |Cite
|
Sign up to set email alerts
|

Filtering for Nonlinear Genetic Regulatory Networks With Stochastic Disturbances

Abstract: Exponential stability analysis for discrete-time switched linear systems with time-delay," Int. J. Innov. Comput., Inform. Control, vol. 3, no. 6, pp. 1557-1564 [7] L. Zhang, P. Shi, and E. Boukas, " H output-feedback control for switched linear discrete-time systems with time-varying delays," Int. J. Control, vol. 80, no. 8, pp. 1354Control, vol. 80, no. 8, pp. -1365Control, vol. 80, no. 8, pp. , 2007 [8] W. P. Dayawansa and C. F. Martin, "A converse Lyapunov theorem for a class of dynamical systems which u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
80
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 133 publications
(80 citation statements)
references
References 31 publications
0
80
0
Order By: Relevance
“…Genetic regulatory networks (GRNs) have been extensively studied in the biological and biomedical sciences, and a large amount of results have been published over the past decade [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Recently, GRNs with time-delays in the form of differential equations have received particular research attention [2,[8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Genetic regulatory networks (GRNs) have been extensively studied in the biological and biomedical sciences, and a large amount of results have been published over the past decade [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Recently, GRNs with time-delays in the form of differential equations have received particular research attention [2,[8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, GRNs with time-delays in the form of differential equations have received particular research attention [2,[8][9][10][11][12][13][14][15][16][17]. It has been revealed that time-delays play a very important role in dynamical modelling of genetic networks, and mathematical models without introducing the delay effects may even provide wrong predictions of the mRNA and protein concentrations [5,6,8].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations